On the impact of the occult on state legitimacy and democratization aid in Africa - Dirk Kohnert (Sociologus, 2020)
The impact of occult belief on legitimacy of the state and on aid for democratization in Africa: Among politicians and development experts in Africa alike there is a growing awareness of the never decreasing importance of the belief in magic and witchcraft on political decision making since pre-colonial times. Demonstration of the control of occult forces as a means of enhancing legitimacy of traditional or charismatic rule had been considered for over a century to be the prerogative of traditional chiefs and their marabouts; now it proved to be effective for the modern political elite and the state as well. An increasing number of African states officially recognized the existence of magic and witchcraft, and they adapted the imposed colonial law accordingly. In addition magic-religious belief systems, as represented by the vodun or African independent churches (e.g. the Kimbanguists), boasting to control witchcraft, are promoted by African political leaders to enhance legitimacy both of the political class and of state governance. At the same time, development experts tried to take into account the socio cultural dimension of development; they called for an "endogenization" of development aid. This call was justified, because endogenization should be considered as a pre-requisite of sustainable aid; however, under certain conditions it may be ambiguous and dangerous as well. Concerning the consideration of occult belief it may lead to the promotion of illegitimate rule and violation of basic human rights. – – Unter Entwicklungsexperten und Politikern in Afrika beginnt sich die Erkenntnis durchzusetzen, daß der Einfluß des Magie- und Hexenglaubens auf den politischen Entscheidungsprozeß seit der Kolonialzeit eher zu- als abgenommen hat. Früher schienen nur traditonelle Herrscher die Demonstration ihrer Macht auch auf dem Gebiet des Okkulten für notwendig zu erachten. Heute bedient sich die modere Elite vieler afrikanischer Länder ebenfalls dieses Mittels, um dem Staat, der Regierung und der herrschenden politischen Klasse in den Augen der Wähler zu mehr Legitimität zu verhelfen. Gleichzeitig sehen sich Entwicklungsexperten und Regierungsberater gehalten, okkulten Glaubenssystemen als integralem Faktor der sozio-kulturellen Dimension der Entwicklung Afrikas zunehmend Beachtung zu schenken. Durch eine "Endogenisierung" der Entwicklungshilfe soll deren Nachhaltigkeit gewährleistet werden. Diese Forderung ist ambivalent und gefährlich: einerseits trägt sie dem berechtigten Interesse der Zielgruppen nach Respektierung ihrer Kultur Rechnung, andererseits kann beispielsweise die offizielle Verankerung des Okkulten im Rechtssystem und in der Politik afrikanischer Staaten zu gravierenden Verletzungen grundlegender Menschenrechte führen.
Additional information: Überarbeitete Englische Fassung von Kohnert, Dirk: (1997): Zum Einfluß des Okkulten auf staatliche Legitimität und Demokratisierungshilfe in Afrika, Sociologus, 47.1997.1, S. 24-50.
Keywords: F35; N37; N97; O17; O29; O35; Z12; Z13; 330; Religion; Entwicklung; Hexenanklagen; Okkulte Glaubenssysteme; Entwicklungshilfe; Sub-Sahara Afrika; Togo; Nigeria; Südafrika; Guinea-Bissau